DESIGN AND IMPLEMENTATION OF A MOBILE FINGERPRINT ATTENDANCE SYSTEM FOR STUDENT AND LECTURERS - Usiobaifo, Agharese Rosemary; Osaseri, Roseline Oghogho (FUDMA JOURNAL OF SCIENCES, 2025)
This study addresses the inefficiencies of traditional attendance tracking methods in educational institutions by developing a mobile fingerprint-based attendance system. Built with Android Studio, Java, and Firebase, the system automates attendance verification during examinations, providing improved accuracy and security. Students register their fingerprints, which are securely stored, and use the mobile app to authenticate their attendance in real-time. This reduces administrative workload, minimizes errors, and enhances overall efficiency. The system’s object-oriented design ensures scalability and maintainability, offering a comprehensive solution to streamline attendance tracking at the University of Benin.